2020
DOI: 10.1038/s41467-020-14959-w
|View full text |Cite
|
Sign up to set email alerts
|

Sex and APOE ε4 genotype modify the Alzheimer’s disease serum metabolome

Abstract: Late-onset Alzheimer's disease (AD) can, in part, be considered a metabolic disease. Besides age, female sex and APOE ε4 genotype represent strong risk factors for AD that also give rise to large metabolic differences. We systematically investigated group-specific metabolic alterations by conducting stratified association analyses of 139 serum metabolites in 1,517 individuals from the AD Neuroimaging Initiative with AD biomarkers. We observed substantial sex differences in effects of 15 metabolites with partia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
193
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 145 publications
(214 citation statements)
references
References 78 publications
19
193
2
Order By: Relevance
“…In our previous publication using p180 data from the ADNI cohort, we reported PC ae C44:4, PC ae C44:5, and PC ae C44:6 were all associated with CSF Aβ pathology, and PC ae C44:4 and PC ae C44:5 were further associated with brain glucose metabolism as measured by FDG PET (18). Effect directions were consistent with our current findings.…”
Section: Phosphatidylcholinessupporting
confidence: 91%
“…In our previous publication using p180 data from the ADNI cohort, we reported PC ae C44:4, PC ae C44:5, and PC ae C44:6 were all associated with CSF Aβ pathology, and PC ae C44:4 and PC ae C44:5 were further associated with brain glucose metabolism as measured by FDG PET (18). Effect directions were consistent with our current findings.…”
Section: Phosphatidylcholinessupporting
confidence: 91%
“…In humans, the prevalence of AD or other dementias is 11% in males and 16% in females at the age of 71 and older, respectively [81]. This discrepancy might be due to the longer life-span of women or related health factors as well as interactions between genetic factors and sex hormones [82][83][84]. However, the causes of the observed discrepancy remain unclear.…”
Section: Biomed Research Internationalmentioning
confidence: 99%
“…The consistent failure of clinical trials focused on reducing Aβ levels and aggregation suggests that such therapies may not work in AD patients regardless of disease stage, underscoring the need to discover novel targets and therapies for AD 1,2 . Recent studies demonstrated that altered energy homeostasis associated with reduced cerebral glucose uptake and utilization, altered mitochondrial function and microglia and astrocyte activation might underlie neuronal dysfunction in AD [3][4][5][6][7] . Intriguingly, accumulating evidence suggests that non-pharmacological approaches, such as diet and exercise, reduce major AD hallmarks by engaging an adaptive stress response that leads to improved metabolic state, reduced oxidative stress and inflammation, and improved proteostasis 8 .…”
mentioning
confidence: 99%